Co-curriculum merit calculation system for school (e-CoMCS) /Nurul Ardiyanna Zainodin - Zainodin, Nurul Ardiyanna (2014)
e-CoMCS is a system that systematically integrates the merit calculation and evaluation of reputation for students. There are two problems that occurred in current situation. First, most of the secondary school is using manual calculation and second, no evaluation for co-curriculum students’ reputation. The objectives of e-CoMCS are to identify requirement of merit calculation co-curriculum for schoof to develop a systemjto help teacher evaluate the merits ofstudents and evaluate the usability of the system. This system will be access by students, advisor and coordinator of co- curriculum clubs. To make it functioning effectively, e-CoMCS uses one technique which is Simple Additive Weighting (SAW) method. It is used to calculate the ranking of the student’s performance. Waterfell model is used to design the system from the beginning to the end. In evaluating the system, the quantitative data analysis was conducted to evaluate the system in such of user interface, usability, ease of use and accuracy. The data findings were assembled through the questionnaire survey with 30 respondents. Construct with the highest result is regarding the content with 70% respondents are agree with it and mode for this indicators 4. The highest mean based on user feedback for this construct is item D2 (Mean = 4.1, SD = 0.5477). This indicates that, the respondents are agreeing with the content in this system because the information provided in this system is helpful for them and user knows where to find the information needed.